The diagram development for Computer Added Control and Monitoring system of drilling - Epikhin A. V. Anton Vladimirovich; Mikhalev R. S.; Anisimov A. V.; Ulyanova O. S. Oksana Sergeevna (Latest Technology of Oil and Gas Driling, 2015)
Title screen